2006
DOI: 10.1007/s00330-006-0383-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Detector row CT urography on a 16-row CT scanner in the evaluation of urothelial tumors

Abstract: The purpose of this study was to assess the role of multi-detector row CT urography (MDCTU), on a 16-row CT scanner in the evaluation of patients with painless hematuria, with emphasis placed in the detection of urothelial tumors. We retrospectively reviewed the MDCT urographies of 75 patients, referred for painless hematuria. The CT protocol included unenhanced images, obtained with a detector configuration of 16x1.5 mm and pitch of 1.2, nephrographic and excretory-phase images, obtained with a detector colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 25 publications
0
31
1
5
Order By: Relevance
“…Last, DECT urography did not expose more radiation to patients than single-energy CT urography. Several studies reported that mean effective dose ranges 20-30 mSv at single-energy CT urography [20][21][22]. This dose is slightly higher than that in our study (16.3 mSv).…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Last, DECT urography did not expose more radiation to patients than single-energy CT urography. Several studies reported that mean effective dose ranges 20-30 mSv at single-energy CT urography [20][21][22]. This dose is slightly higher than that in our study (16.3 mSv).…”
Section: Discussioncontrasting
confidence: 74%
“…All patients underwent threephase CT imaging to scan the area between the liver and symphysis pubis. First, a UCT scan was acquired and then nephrographic and excretory CT scans were performed at 100 s and 8 min (n529) or 12 min (n53) after intravenous injection of 120 ml contrast material (ultravist 300; Bayer Schering Pharma, Berlin, Germany) at the rate of 3 ml s 21 . Prior to the 8 min excretory CT, furosemide was administered to 29 patients.…”
Section: Ct Imagingmentioning
confidence: 99%
“…Studies focusing on CTU in patients with microscopic haematuria show that causes for haematuria are identified in 33.0-42.6% with overall CTU sensitivity for identification of the cause of haematuria of 92.4-100% and specificity of 89.0-97.4% [8][9][10][11][12][13]. In studies on microscopic or unselected haematuria upper tract TCC was present in 0.9-7.3% [8,11,14].…”
Section: Indicationsmentioning
confidence: 98%
“…Renal parenchymal abnormalities, particularly masses, are best visualized on nephrographic phase images, which also provide excellent evaluation of the other abdominal organs. Excretory phase images obtained from the kidneys to the bladder demonstrate the urinary tract distended with contrast material and are useful in detecting papillary/ calyceal abnormalities as well as urothelial disease [1,11,12]. Although CT may also demonstrate bladder disease, flat tumors of the bladder are unlikely to be identified with CT, and cystoscopy remains the study of choice in evaluating for bladder malignancy.…”
Section: Introductionmentioning
confidence: 97%
“…Dose management technology in CT has led to optimization of CT protocols using angular (x and y-axes), longitudinal (z-axis), or combined (x, y, and z-axes) modulation of the dose; in some modern systems, this can also be combined with 3D adaptive noise filtration [1,11,12].…”
Section: Introductionmentioning
confidence: 99%